RETRACTED: CHOICE OF OSTEOFIXATION OF EPITHESIS IN TOTAL DEFECT OF THE MAXILLOFACIAL REGION - N. I. Tcherezova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
RETRACTED ARTICLERelevance. Surgical treatment of neoplasms, various genetic disorders and facial trauma often contribute to a violation of the general aesthetic perception of a person and the development of dysfunctions [1]. The main difficulty of reconstructive treatment in the maxillofacial area is a clear understanding of the anatomical and topographic landmarks and three-dimensional relationships of organs and tissues from each other. Purpose. Development of an algorithm for the use of various types of extraoral implants for various total facial defects. Materials and methods. The collection and analysis of clinical material was carried out in the Department of Maxillofacial Surgery on the basis of the Samara Regional Clinical Hospital  named after V.I. V.D. Seredavina. From 2015 to the present, we have installed 104 extraoral implants of various designs for the rehabilitation rehabilitation of fifty patients suffering from total facial defects of various lengths. Conclusions. The analysis of our study showed that the use of extraoral implants of various designs for total facial defects of various lengths, taking into  account individual anatomical and topographic features, the etiology of  the total defect, has demonstrated its clinical effectiveness.